ANALISIS KUALITAS PELAYANAN YANG MEMBEDAKAN KEPUASAN DAN KETIDAKPUASAN PELANGGAN TELKOM FLEXI - Muis, Mahlia (Fakultas Ekonomi, UIN Maliki Malang, 2009)
This research was conducted based on the fact that service quality plays an important role on determining the difference between satisfaction and dissatisfaction customers. The research findings indicate, using discriminant analysis with force method, it shows that significant difference between satisfaction and dissatisfaction customers in terms of service quality (tangibility, reliability, responsiveness, assurance, and emphaty).